Pendapatan Usahatani Kembang Kol Musim Kemarau dan Musim Hujan di Kabupaten Tanggamus - Putri, Rafika Dila; Prasmatiwi, Fembriarti Erry; Haryono, Dwi (Universitas Galuh, 2025)
Low cauliflower productivity in Tanggamus Regency not only reduces farm income but also has an impact on farmers' household income. The purpose of this study was to analyze farm income in the dry and rainy seasons and the share of cauliflower farming income to household income. The location of the study was in the cauliflower production center, namely Gisting District and Gunung Alip District. The population of cauliflower farmers was 82 people, and all of them were taken as samples in this study. The research data were taken from October to December 2024. The analysis method used was quantitative descriptive analysis, namely farm income analysis and household income analysis. The results of this study indicate that cauliflower farming in both seasons is profitable, but the rainy season is lower than the dry season. The total income of farmer households is IDR 62,201,587.76/year and the share of cauliflower farming income to the total income of farmer households is 22.55%.